2021
DOI: 10.7150/jca.53215
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific Risk Factors for Pelvic Lymph Node Metastasis in Patients with Stage IB1 Cervical Cancer

Abstract: Objectives: We aimed to identify the risk factors associated with pelvic lymph node metastasis (LNM) at each anatomic location in patients with stage IB1 cervical cancer. Methods: A primary cohort of 728 patients with stage IB1 cervical cancer who underwent radical hysterectomy and systematic pelvic lymphadenectomy were retrospectively studied. All removed pelvic nodes (N=20,134) were pathologically examined. The risk factors for LNM in different anatomic regions (obturator, internal iliac, external iliac, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Our previous study found that 14.6% of patients with early-stage CCa had LNM before surgery [ 11 ]. However, traditional imaging techniques are not sufficiently reliable to detect LNM (in a meta-analysis, the pooled sensitivity was 0.57 for computed tomography, 0.66 for positron emission tomography and 0.54 for magnetic resonance imaging) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that 14.6% of patients with early-stage CCa had LNM before surgery [ 11 ]. However, traditional imaging techniques are not sufficiently reliable to detect LNM (in a meta-analysis, the pooled sensitivity was 0.57 for computed tomography, 0.66 for positron emission tomography and 0.54 for magnetic resonance imaging) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have well established risk factors for node involvement, such as tumor size larger than 20 mm, the presence of lymphovascular space invasion (LVSI), deeper stromal invasion and parametrial involvement [ 8 , 9 , 10 , 11 , 12 ]. Nonetheless, results of these studies are based on final pathologic examination of radical hysterectomy specimens and are usually extrapolated for preoperative risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prognosis differed in patients with different LNM locations or numbers (LNM involving the common iliac region vs lower regions, ≥3 vs 1–2, respectively). 24 , 26 Therefore, as in our study, it is reasonable to refine stage IIIc into subgroups according to the LNM degree and location.…”
Section: Discussionmentioning
confidence: 72%